DEVELOPMENT OF AN IOT-ENABLED NOISE MONITORING AND CONTROLLING DEVICE WITH ADVANCED ALERT MECHANISM FOR SILENT ZONE AREAS IN INDIA: OVERCOMING IOT CHALLENGES AND ENHANCING QUALITY OF LIFE - Rajesh A. Sanadi; Dr. Avaneesh Anand Singh (International Journal For Research In Advanced Computer Science And Engineering, 2023)
Noise pollution has become a pervasive environmental issue in urban and semi-urban areas, significantly affecting the quality of life and health of individuals. Silent zones, such as hospitals, schools, court areas, and libraries, are especially vulnerable to noise disturbances due to their requirement for tranquillity to facilitate healing, learning, and concentration. According to Singh and Davar (2004), excessive noise levels in silent zones can lead to increased stress, reduced cognitive performance, and even long-term health complications like cardiovascular diseases. These effects highlight the critical need for effective noise monitoring and control mechanisms in such areas. The importance of monitoring and controlling noise cannot be overstated. Kumar et al. (2018) emphasized that a well-implemented noise control system can not only ensure compliance with regulatory standards but also significantly enhance the well-being of occupants in silent zones. Real-time monitoring devices with advanced features, such as alert mechanisms and automated controls, are essential to achieve this goal, especially in environments that demand uninterrupted focus or recovery.